Growth analysis in forage sorghum in two planting periods - Pérez Hernández, Alejandra; Carrillo, Adrián Raymundo Quero; Velázquez, Santiago Garduño; Estrada, José Alberto Salvador Escalante; González, María Teresa Rodríguez; Jiménez, Leonor Miranda (Revista Mexicana de Ciencias Agrícolas, 2019)
Growth analysis is a periodic quantification of dry matter yield that allows to determine the optimum cutting moment. The objective was to know the growth, to quantify the accumulation of dry matter in a time interval, in four varieties of forage sorghum: Caña dulce, Silo miel, Esmeralda and Fortuna, similarly, to determine phenology, in two periods of sowing: tip of irrigation (April-October) and rains (June-December) in Montecillo, Texcoco, State of Mexico. Phoenology was determined, height of plant (AP), number of leaves (NDH), number of stems (NDT), number of knots per plant (NDP), yield of dry matter (RMS), leaf area index (IAF), leaf area duration (DAF), crop growth rate (TCC) and net assimilation rate (TAN) was calculated. The experimental design complete randomized blocks with factorial arrangement and four repetitions, significant variables, were compared with the Tukey test (p≤ 0.05). Caña dulce presented higher AP (210 cm) in both periods, at 145 days after the average sowing (dds); NDT (33), NDH (8.1), NDN (8.3); TCC (24 g m-2 d-1 to 75(dds) and 26 g m-2 d-1 to 84 dds), TAN (19.1 g m-2 d-1 and 13.8 g m-2 d-1 from emergency to 20 dds); the above, resulted in higher yields (p≤ 0.05) per square meter (15.7 and 15.5 t DM ha-1) at the point of irrigation and the rainy season, respectively. The Silo miel cultivar showed higher IAF with 5 to 125 dds and 4.6 to 120 dds and DAF of 114 days; the above, for irrigation tip and rainfall, respectively. The best cultivar for the region was Caña dulce.
Keywords: Sorghum bicolor (L.) Moench; phenology; rainfall; yield